Nuchal translucency: an ultrasound marker for fetal chromosomal abnormalities - Acácio, Gregório Lorenzo; Barini, Ricardo; Pinto Júnior, Walter; Ximenes, Renato Luís Silveira; Pettersen, Heverton; Faria, Marcos (São Paulo Medical Journal, 2001)
CONTEXT: The literature shows an association between several ultrasound markers and chromosome abnormality. Among these, measurement of nuchal translucency has been indicated as a screening method for aneuploidy. The trisomy of chromosome 21 has been most evaluated. OBJECTIVE: To define the best fixed cutoff point for nuchal translucency, with the assistance of the ROC curve, and its accuracy in screening all fetal aneuploidy and trisomy 21 in a South American population. TYPE OF STUDY: Validation of a diagnostic test. SETTING: This study was carried out at the State University of Campinas, Campinas, Brazil. PARTICIPANTS: 230 patients examined by ultrasound at two tertiary-level private centers, at 10 to 14 weeks of gestation. DIAGNOSTIC TEST: The participants consisted of all those patients who had undergone ultrasound imaging at 10 to 14 weeks of gestation to measure nuchal translucency and who had had the fetal or neonatal karyotype identified. MAIN MEASUREMENTS: Maternal age, gestational age, nuchal translucency measurement, fetal or neonatal karyotype. RESULTS: Prevalence of chromosomal defects – 10%; mean age – 35.8 years; mean gestational age – 12 weeks and 2 days; nuchal translucency (NT) thickness – 2.18 mm. The best balance between sensitivity and specificity were values that were equal to or higher than 2.5 mm for overall chromosomal abnormalities as well as for the isolated trisomy 21. The sensitivity for overall chromosomal abnormalities and trisomy 21 were 69.5% and 75%, respectively, and the positive likelihood ratios were 5.5 and 5.0, respectively. CONCLUSION: The measurement of nuchal translucency was found to be fairly accurate as an ultrasound marker for fetal abnormalities and measurements equal to or higher than 2.5 mm were the best fixed cutoff points.